2009
DOI: 10.1007/s12010-008-8518-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the C–H…O Interactions in Glycoproteins

Abstract: Glycoproteins are an important class of proteins that play a significant role in many cellular events. In the present study, we analyze the influence of C-H...O interactions in relation to other environmental preferences in glycoproteins. CH...O interactions are now accepted as a genuine hydrogen bond. Main chain-main chain interactions are predominant. Proline residues stabilize strands by C-H...O interactions in glycoproteins. Majority of the C-H...O interacting residues were conserved and had one or more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…The higher percentage of CHÀO interactions may be explained in terms of the larger abundance of CH groups. These results were similar to that of the results observed with RNA binding proteins, [48] antimicrobial peptides, [49] interleukins, [17] Glycoproteins [50] and thermophilic proteins [51] where the CHÀO interactions are the predominant type of interactions. It is interesting to note that, our results were somewhat different to that of the results observed with RNA binding proteins [48] where the major contribution to CHÀO interactions was mainly from main-chain interactions.…”
Section: Distribution Of Non-canonical Interactionssupporting
confidence: 90%
See 3 more Smart Citations
“…The higher percentage of CHÀO interactions may be explained in terms of the larger abundance of CH groups. These results were similar to that of the results observed with RNA binding proteins, [48] antimicrobial peptides, [49] interleukins, [17] Glycoproteins [50] and thermophilic proteins [51] where the CHÀO interactions are the predominant type of interactions. It is interesting to note that, our results were somewhat different to that of the results observed with RNA binding proteins [48] where the major contribution to CHÀO interactions was mainly from main-chain interactions.…”
Section: Distribution Of Non-canonical Interactionssupporting
confidence: 90%
“…Recently, Stojanović et al [50] reported that the fractional distribution of hydrophobic, hydrophilic and charged residues contributed to the solvent accessible protein surface and to the interfaces in Sm proteins. The surfaces contained 29 % hydrophobic amino acids, 28 % hydrophilic, and 43 % charged residues.…”
Section: Residue Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Non-canonical interactions, such as C-H· · · O interactions, have gained much attention, with a number of studies emphasizing the importance of these unconventional hydrogen bonds in stabilizing the structure of proteins [6]. The importance of C H· · · O interactions in biological structures is also evident from the early analysis of C H· · · O interactions in glycoproteins [7], RNA binding proteins [8], protein-DNA recognition [9], and carbohydrate-lectin interactions [10]. In 1996, Bella and Berman identified the importance of C H· · · O interactions in a collagen triplex helix [11].…”
Section: Introductionmentioning
confidence: 99%